Resistance to First-Line Anti-TB Drugs Is Associated with Reduced Nitric Oxide Susceptibility in Mycobacterium tuberculosis - Idh, Jonna; Mekonnen, Mekidim; Abate, Ebba; Wedajo, Wassihun; Werngren, Jim; Ängeby, Kristian; Lerm, Maria; Elias, Daniel; Sundqvist, Tommy; Aseffa, Abraham; Stendahl, Olle; Schön, Thomas (PLOS ONE, 2012)
Background and Objective The relative contribution of nitric oxide (NO) to the killing of Mycobacterium tuberculosis in human tuberculosis (TB) is controversial, although this has been firmly established in rodents. Studies have demonstrated that clinical strains of M. tuberculosis differ in susceptibility to NO, but how this correlates to drug susceptibility and clinical outcome is not known. Methods In this study, 50 sputum smear- and culture-positive patients with pulmonary TB in Gondar, Ethiopia were included. Clinical parameters were recorded and drug susceptibility profile and spoligotyping patterns were investigated. NO susceptibility was studied by exposing the strains to the NO donor DETA/NO. Results Clinical isolates of M. tuberculosis showed a dose- and time-dependent response when exposed to NO. The most frequent spoligotypes found were CAS1-Delhi and T3_ETH in a total of nine known spoligotypes and four orphan patterns. There was a significant association between reduced susceptibility to NO (>10% survival after exposure to 1 mM DETA/NO) and resistance against first-line anti-TB drugs, in particular isoniazid (INH). Patients infected with strains of M. tuberculosis with reduced susceptibility to NO showed no difference in cure rate or other clinical parameters but a tendency towards lower rate of weight gain after two months of treatment, independent of antibiotic resistance. Conclusion: There is a correlation between resistance to first-line anti-TB drugs and reduced NO susceptibility in clinical strains of M. tuberculosis. Further studies including the mechanisms of reduced NO susceptibility are warranted and could identify targets for new therapeutic interventions.